2016
DOI: 10.1111/eos.12305
|View full text |Cite
|
Sign up to set email alerts
|

High fear of intra-oral injections: prevalence and relationship to dental fear and dental avoidance among 10- to 16-yr-old children

Abstract: The present study aimed to: (i) estimate the prevalence of self-reported high fear of intra-oral injections, high blood-injury fear, and injection fear; (ii) explore the overlap between high fear of intra-oral injections and high fear of dental treatment; and (iii) evaluate the possible consequence of high fear of intra-oral injections in terms of avoidance of dental care. The sample included 1,441 subjects, 10- to 16-yr of age, attending elementary schools in a county of Norway. Data were collected using ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Therefore, we could not obtain information on the reasons for non-participation. However, the results on the prevalence of DFA (CFSS-DS) and intra-oral injection fear (IOIF-s) did not differ substantially from a representative study in a similar population with a high response rate (Berge et al 2016). One weakness of our study is the application of seven non-validated items regarding restraint.…”
Section: Limitationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, we could not obtain information on the reasons for non-participation. However, the results on the prevalence of DFA (CFSS-DS) and intra-oral injection fear (IOIF-s) did not differ substantially from a representative study in a similar population with a high response rate (Berge et al 2016). One weakness of our study is the application of seven non-validated items regarding restraint.…”
Section: Limitationsmentioning
confidence: 60%
“…We adopted the term ‘DFA’ to describe all levels of dental fear and anxiety given that the terms ‘fear’ and ‘anxiety’ are often used interchangeably by clinicians. Approximately 5–20% of children and adolescents experience high DFA or high fear of intra-oral injections, with the variation attributed to differences in study populations and study design (Berge et al 2016 ; Klingberg and Broberg 2007 ; Stenebrand et al 2013 ). In the adult population, DFA is associated with reduced oral health (Hakeberg et al 1993 ) and quality of life (Berggren 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…In his study, Berge et al demonstrated that high fear of intraoral injections was prevalent and might lead to avoidance of necessary dental treatment. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Needle fear can be a barrier to receipt of healthcare interventions, including routine vaccinations for preventable serious diseases such as hepatitis B and measles, blood tests and intravenous medications [5,6]. Fear of intra-oral injections has been reported as a specific barrier to both adults and children receiving dental treatment [7,8]. The concept of needle fear amongst those with dental anxiety is not a new one, with a 1988 Japanese study identifying the injection as one of the most stressful elements and a 1995 study of low income American families confirming that injection is a main theme in relation to dental anxiety in children [9,10].…”
Section: Introductionmentioning
confidence: 99%